2016
DOI: 10.3389/fonc.2016.00063
|View full text |Cite
|
Sign up to set email alerts
|

The Application and Outcome of Standard of Care Treatment in Elderly Women with Ovarian Cancer: A Literature Review over the Last 10 Years

Abstract: The rising number and increasing longevity of the elderly population calls for improvements and potentially a more personalized approach to the treatment of cancer in this group. Elderly patients frequently present with a number of comorbidities, complicating surgery and chemotherapy tolerability. In the case of ovarian cancer, elderly women present with more advanced disease, making the issue of providing adequate treatment without significant morbidity critical. Most studies support the application of standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 58 publications
1
34
1
Order By: Relevance
“…Furthermore, we found chemo-duration to be significantly prolonged in patients older than 58 years of age when compared to younger patients. This might reflect difficulties for the administration of chemotherapy in the elderly cancer patient [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found chemo-duration to be significantly prolonged in patients older than 58 years of age when compared to younger patients. This might reflect difficulties for the administration of chemotherapy in the elderly cancer patient [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite significant advancements in cancer therapeutics over the past several decades, relapse following long periods of remission after treatment remains a persistent problem in EOC (18,19). Fatal recurrences for patients with EOC can arise years and even decades later, often in the form of metastatic disease, the major cause of cancer-related deaths (20,21). We found that low MED12 expression was associated with chemotherapy resistance in patients with EOC and MED12 KO in EOC cells would induce tumor cell dormancy.…”
Section: Discussionmentioning
confidence: 78%
“…With the improvement in population age and life expectancy, the increasing number of patients has altered the demographics of EOC. Therefore, age-oriented factors related to prognosis in ovarian cancer should be determined [10,11].…”
Section: Introductionmentioning
confidence: 99%